THE CRAB SILVOFISHERY SYSTEM AS A CONSERVATION STRATEGY IN MANGROVE RESTORATION AREA: A CASE STUDY ON THE COAST OF BANYUASIN, SOUTH SUMATRA - Apriyanto, Apriyanto; Suwignyo, Rujito Agus; Ulqodry, Tengku Zia; Sarno, Sarno; Aryawati, Riris; Muhtadi, Muhtadi; Purnomo, Herry; Okarda, Beni (UI Scholars Hub, 2025)
Anthropogenic activities such as logging and converting mangrove forests into plantations have degraded coastal ecosystems and reduced their ecological stability. Silvofishery is a restoration system that balances the ecological and economic functions of mangroves. In Marga Sungsang Village, South Sumatra, mangrove restoration was integrated with mud crab (Scylla spp.) cultivation through a crab silvofishery system. This study aimed to analyze the contribution of mangrove restoration with a mud crab silvofishery system to mud crab growth. The study was conducted from August 2024 to January 2025. Growth parameters included carapace length, width, and body weight. Analyses covered absolute growth and the correlation between carapace width and body weight. Results showed that in non-mangrove ponds, Scylla tranquebarica males exhibited negative allometry (prominent carapace width), while females showed positive allometry (prominent body weight). Scylla paramamosain showed negative allometry in both sexes. In contrast, in mangrove ponds, both species showed positive allometry for both sexes, indicating higher weight gain. These findings suggest that mangrove vegetation provides optimal habitat conditions by increasing nutrient availability, protecting crabs during molting, and improving substrate quality. The results not only demonstrate the bioecological relationship between mangrove vegetation and mangrove crab growth but also highlight the role of crab silvofishery systems in supporting food security, mitigating climate change, and conserving coastal ecosystems. These results align with the Sustainable Development Goals (SDGs), specifically goal 2 (end hunger, achieve food security and improved nutrition, and promote sustainable agriculture), goal 13 (climate action), and goal 14 (life below water). Although informative, this study was limited by temporal observations conducted only at the start of seed stocking and at harvest. Further research with continuous monitoring and environmental parameter analysis is needed. The findings can support mangrove restoration policies that integrate vegetation recovery with sustainable community-based aquaculture and promote blue economy development.